Penyuluhan Moderasi Beragama pada Ibu-Ibu Majelis Taklim Mesjid Asy-Syamsu Karyamulta untuk Menangkal Radikalisme - Kurnia, Rina; Maldini, Rizqiana (Lembaga Pengabdian kepada Masyarakat Universitas Langlangbuana, 2023)
Indonesia has experienced various incidents such as terror, bombings and hostage-taking as a result of acts of terrorism committed by people who are radical and intolerant of differences. It cannot be denied that Indonesia is a pluralistic country with differences in ethnicity, customs, language and religion. Thus, in 2019, the Government of Indonesia seeks to strengthen religious moderation as a concept for preventing and overcoming terrorism and radicalism. Majlis taklim as a non-formal educational institution is the main target in strengthening religious moderation, especially for mothers who have a desire to study religion. Therefore, counseling on religious moderation was given to the ladies of the taklim assembly of the Asy-Syamsu Mosque, Karyamulya, Cirebon City which coincided with RT/RW 02/05. The activity was carried out in two stages which included observation and interviews as well as providing counseling. The results achieved from the implementation of this activity were: (1) increased insight and understanding of the women of the Asy-Syamsu Mosque taklim assembly regarding religious moderation, (2) knowing the flow of coordination when they saw something odd, and (3) the women of the taklim assembly Asy-Syamsu Mosque has awareness to process the information obtained. This activity is expected to provide benefits to the community, especially the women of the Asy-Syamsu Mosque taklim assembly.